DEVELOPMENT OF COMMUNICATIVE SKILLS IN FUTURE TEACHERS AS A PEDAGOGICAL PROBLEM (International journal of artificial intelligence, 2025)
In this article, the issues of communicative competence, the development of professional competence of future teachers, the unity of the three interrelated communicative, interactive and perceptual components in communication, the teacher's professional communicative competence, communicative self-improvement, higher pedagogy training sessions.